Internalization of Entrepreneurship Values in the Market Day Program as a Form of Application of Islamic Religious Education Values - Atik Rosanti; Kardi Kardi; Uus Ruswandi; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the internalization of entrepreneurship values ​​in the market day program as a form of application of the values ​​of Islamic religious education. The method used in this study uses a library method or approach, that literature or literature study can be interpreted as a series of activities related to methods of collecting library data, reading and recording and processing research materials. The results of this study indicate that students are also very creative, even before the market day, all students take the initiative to make posters and stick them on the school walls to promote their wares. This market day program is the same as buying and selling that is carried out in markets in general. The difference here is that the salespeople are children. With this program, of course, it can train students' self-confidence and creativity. The process of internalizing Islamic values ​​has been instilled, not only in the market day program, internalization of Islamic values ​​has also been instilled from students in class I to everyday life, through the market day program the teacher exemplifies buying and selling in Islam.